Malaysia's strategic food security approach - Tey, Yeong Sheng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
This paper is interested in exploring the interrelatedness of some accompanying policy changes and initiatives in the selected Asian countries as well as reviewing the Malaysian National Food Security Policy. Actions taken in response to the food crisis in the selected Asian countries have worked out well and produced promising outcomes from a combination of availability, accessibility, utilization, and stability aspects in food security. Malaysia weighted more on availability aspect in food security by introducing more short- and long- term policy measures for boosting paddy and rice production, particularly in Sabah and Sarawak under the National Food Security Policy. However, much of the unhappiness and disequilibrium in the local paddy and rice market were created due to irrational extensive intervention of the Miller Subsidy and Beras Nasional programmes in the nation. Many of the policy measures targeted at area expansion and productivity but it was suggested that the dominant path to achieve the targeted self-sufficiency level is through research and development at specialized and committed paddy and rice research centre. Trade oriented self-reliance approach that strategized with multiple and diversified sources of rice import was tipped to be superior of current self-sufficiency approach.